Exploring the STEP-uP to practice: A survey of UK Lead Midwives for Education views of the STudent midwife Extended Practice Placement during the first wave of the COVID-19 pandemic. (October 2021) - Cooke, Alison; Hancock, Angela; White, Helen; Clark, Nicky; Gibb, Fiona; McNeill, Jenny; Thomas, Grace; Lloyd, Carmel; Furber, Christine
Highlights: Midwifery education was affected by national regulatory changes early in the pandemic. There was variation in how the extended placement option was implemented. UK AEIs provided midwifery students with the majority of decisional support. LMEs experienced both internal and external pressures to instigate rapid change. Learning can be taken from the impact of COVID-19 on midwifery education. Abstract: Objective: to assess the effect of implementation of the extended placement option available to midwifery students during the first wave of the COVID-19 pandemic. Design: Online survey open from 2nd June 2020 to 15th July 2020. Setting: United Kingdom. Participants: Lead Midwives for Education (LMEs). Findings: A total of 38 of 55 LMEs responded (response rate 69%). The majority of Approved Education Institutions (AEIs) offered an extended placement to students, but with some variation in the choices offered, unrelated to geographical location or size of student cohort. AEIs appeared to provide the majority of decisional support for students. Many practice learning environments became unavailable, particularly community, gynaecology/medical wards and neonatal units. LMEs experienced both internal and external pressures to instigate rapid change. Key conclusions: The impact of COVID-19 on midwifery education is significant and will need continual scrutiny to minimise future detriment. The pressures of providing midwifery education throughout the early phase of COVID-19 were substantial, but it is important that we learn from the immediate changes made, value and pursue the changes that have been beneficial, and learn from those that were not. Implications for Practice/Research: Student learning experiences have undergone significant change during the pandemic. It is essential to assess what effect the extended placement has had on student readiness for practice, their confidence, resilience, mental health, and attrition and retention. Educators transitioned to remote working, and rapidly assimilated new skills for online education; exploration of the impact of this is recommended.